Genetic Diversity of Clinical and Environmental Isolates of Vibrio cholerae Determined by Amplified Fragment Length Polymorphism Fingerprinting - Jiang, Sunny C. (American Society for Microbiology, 2000)
Vibrio cholerae, the causative agent of major epidemics of diarrheal disease in Bangladesh, South America, Southeastern Asia, and Africa, was isolated from clinical samples and from aquatic environments during and between epidemics over the past 20 years. To determine the evolutionary relationships and molecular diversity of these strains, in order to understand sources, origin, and epidemiology, a novel DNA fingerprinting technique, amplified fragment length polymorphism (AFLP), was employed. Two sets of restriction enzyme-primer combinations were tested for fingerprinting of V. cholerae serogroup O1, O139, and non-O1, O139 isolates. Amplification of HindIII- and TaqI-digested genomic DNA produced 30 to 50 bands for each strain. However, this combination, although capable of separating environmental isolates of O1 and non-O1 strains, was unable to distinguish between O1 and O139 clinical strains. This result confirmed that clinical O1 and O139 strains are genetically closely related. On the other hand, AFLP analyses of restriction enzyme ApaI- and TaqI-digested genomic DNA yielded 20 to 30 bands for each strain, but were able to separate O1 from O139 strains. Of the 74 strains examined with the latter combination, 26 serogroup O1 strains showed identical banding patterns and were represented by the O1 El Tor strain of the seventh pandemic. A second group, represented by O139 Bengal, included 12 strains of O139 clinical isolates, with 7 from Thailand, 3 from Bangladesh, and 2 from India. Interestingly, an O1 clinical isolate from Africa also grouped with the O139 clinical isolates. Eight clinical O1 isolates from Mexico grouped separately from the O1 El Tor of the seventh pandemic, suggesting an independent origin of these isolates. Identical fingerprints were observed between an O1 environmental isolate from a river in Chile and an O1 clinical strain from Kenya, both isolated more than 10 years apart. Both strains were distinct from the O1 seventh pandemic strain. Two O139 clinical isolates from Africa clustered with environmental non-O1 isolates, independent of other O139 strains included in the study. These results suggest that although a single clone of pathogenic V. cholerae appears responsible for many cases of cholera in Asia, Africa, and Latin America during the seventh pandemic, other cases of clinical cholera were caused by toxigenic V. cholerae strains that appear to have been derived locally from environmental O1 or non-O1 strains.